2020
DOI: 10.1186/s12866-020-02027-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive response to iterative passages of five Lactobacillus species in simulated vaginal fluid

Abstract: Background Microbiome and metagenomic studies have given rise to a new understanding of microbial colonization of various human tissues and their ability to impact our health. One human microbiome growing in notoriety, the vaginal microbiome, stands out given its importance for women’s health, and is peculiar in terms of its relative bacterial composition, including its simplicity and typical domination by a small number of Lactobacillus species. The loss of Lactobacillus dominance is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The small bacterial and fungal growth observed in the control (SVF) was already anticipated due to the poor nutrient availability of SVF as a consequence of its composition. Indeed, comparative analysis of the growth of Lactobacilli and C. albicans in MRS and SVF has showed that these microorganisms have a substantially smaller growth in SVF, as previously reported by Pan et al ( 2020 ), Brandt and Barrangou ( 2020 ) and Fernandes et al ( 2023 ). Contrary, both the growth of Lactobacilli and C. albicans has increased in the presence of MOS Parr and MOS H 3 PO 4 , most likely because they use can use mannose and other components of the MOS extracts.…”
Section: Resultssupporting
confidence: 73%
“…The small bacterial and fungal growth observed in the control (SVF) was already anticipated due to the poor nutrient availability of SVF as a consequence of its composition. Indeed, comparative analysis of the growth of Lactobacilli and C. albicans in MRS and SVF has showed that these microorganisms have a substantially smaller growth in SVF, as previously reported by Pan et al ( 2020 ), Brandt and Barrangou ( 2020 ) and Fernandes et al ( 2023 ). Contrary, both the growth of Lactobacilli and C. albicans has increased in the presence of MOS Parr and MOS H 3 PO 4 , most likely because they use can use mannose and other components of the MOS extracts.…”
Section: Resultssupporting
confidence: 73%
“…A recent study did not find such evolutionary pressure to mutate the amylopullulanase: even after cultivation of up to 1000 generations by sequential sub-culturing in synthetic vaginal fluid, no genetic variations in the pulA locus of strains of L. crispatus were detected [30]. We hypothesize that this may be due to the available carbohydrates in this simulated vaginal fluid, which contains both glucose and glycogen and is further supplemented with amylase which degrades the glycogen into smaller maltodextrins.…”
Section: Discussionmentioning
confidence: 63%
“…Oral supplementation predisposes the vagina to much lower quantities of the supplemented strain(s) than local application; thus, comparable competitive and environmental factors may play an even more significant role. Although L. acidophilus, being a gut-oriented lactobacillus, adapts well to simulated vaginal fluid, it would unlikely be able to successfully compete with abundant endogenous vaginal lactobacilli such as L. crispatus, L. gasseri, and L. jensenii [ 68 ]. Aligned, Chen and colleagues found the effects of an oral probiotic to be more probable in the vaginal microbiota of participants with higher intraindividual variability within the vaginal microbiome already before the intervention commenced, whereas participants with a stable and lactobacilli-rich vaginal microbiota at baseline were more resilient to the effects of the probiotic [ 33 ].…”
Section: Discussionmentioning
confidence: 99%